PROGRAM PENDIDIKAN SEKS UNTUK MENINGKATKAN PROTEKSI DIRI DARI EKSPLOITASI SEKSUAL PADA ANAK USIA DINI - Zarina Akbar; Felianti Mudzdaliffah (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2012)
Sexual violence against the children often occurs as they have not got sex education. Therefore, sex education should be provided to the early-age children and a research is conducted to find out the result. This research aims at knowing the children’s ability to protect themselves from sexual violance. The research conducted at Ar-Rachman Kindergarten, South Jakarta in November 2011 employed quantitative quasi-experiment. The analysis indicates significant difference in the score between pre-test and post-test of the experiment group. Based on the finding, the research concludes that there is a significant difference in self protection ability for the student having achieved sex education program compared to those who have not. The research recommend sex education should be provided for early-aged children to minimize sexual violence.